The Multi-Institutional Experience in Single-Port Robotic Transvesical Simple Prostatectomy for Benign Prostatic Hyperplasia Management. Issue 2 (4th August 2022) - Abou Zeinab, Mahmoud; Beksac, Alp Tuna; Corse, Tanner; Talamini, Susan; Morgantini, Luca; Kaviani, Aaron; Ferguson, Ethan; Eltemamy, Mohamed; Crivellaro, Simone; Ahmed, Mutahar; Stifelman, Michael; Kaouk, Jihad
Abstract : Purpose: Single-port (SP) robotic-assisted simple prostatectomy (RASP) through the transvesical approach is a novel surgical option in the management of large prostatic glands. We present the first multi-institutional study to further assess the perioperative and postoperative outcomes of SP RASP. Materials and Methods: From February 2019 to November 2021, 91 consecutive patients of 3 separate institutions underwent transvesical RASP using the da Vinci® SP robotic surgical system. Surgeries were performed by 3 experienced surgeons. Through a suprapubic incision and transvesical access, the SP robot is docked directly into the bladder, and the prostatic enucleation is performed. Prospective data collection, including baseline characteristics, perioperative and postoperative outcomes, was performed. The mean followup period was 4.6 months. Results: The mean (SD) prostate volume was 156 (62) ml. The mean (SD) total operative time was 159 (45) minutes, and the median (IQR) estimated blood loss was 100 (50, 200) cc. The median (IQR) postoperative hospital stay was 21.0 (6.5, 26.0) hours; however, 42% of all patients were discharged the same day. The median (IQR) Foley catheter duration was 5 (5, 7) days. Only 3 patients (3%) developed Clavien grade 2 postoperative complications. At 9-month followup, the median (IQR) International Prostate Symptom Score and quality of life score were 4 (2, 5) and 0 (0, 1), respectively, with a mean (SD) maximum flow rate and post-void residual of 21 (17) ml/second and 40 (55) ml, respectively. Conclusions: In a multi-institutional setting, the SP RASP promotes a pain-free procedure, same-day discharge, short Foley catheter duration, low complication rate and quick recovery.